The Toll-like receptor 4 polymorphism Asp299Gly but not Thr399Ile influences TLR4 signaling and function. - Huaicong Long; Brian P O'Connor; Rachel L Zemans; Xiaofang Zhou; Ivana V Yang; David A Schwartz (PLoS ONE)
The common, co-segregating Toll-like receptor 4 (TLR4) non-synonymous single nucleotide polymorphisms (SNPs), Asp299Gly and Thr399Ile, are associated with hyporesponsiveness to inhaled lipopolysaccharide (LPS) and increased susceptibility to Gram negative pathogens in humans. The purpose of this study was to identify the relative contributions of the Asp299Gly and the Thr399Ile variants in inhibiting the function of TLR4. 293/hMD2-CD14 cell line was transfected with lentiviral constructs containing human wild type (WT) TLR4-EGFP or TLR4-EGFP with Asp299Gly, Thr399Ile or Asp299Gly/Thr399Ile complementary DNA (cDNA). Multiple stable cell lines were established for each construct: three for WT TLR4, Asp299Gly, and Thr399Ile, and only two for Asp299Gly/Thr399Ile mutants and EGFP control. We did not observe a significant effect of polymorphisms on cell surface and intracellular TLR4 expression nor were there any significant differences in TLR4 and EGFP protein levels assessed by Western blotting and confocal microscopy among the multiple cell lines of each of the constructs. All cell lines had a dose-dependent responsiveness to LPS stimulation. However, compared to the WT TLR4, cells expressing TLR4 with Asp299Gly but not Thr399Ile polymorphism produced significantly less (P<0.05) IL-8 following LPS stimulation. Similarly, cells expressing TLR4 Asp299Gly but not Thr399Ile allele had significantly lower percentage of phosphorylated and total NF-κB P65 following LPS stimulation. While we could not do statistics on the Asp299Gly/Thr399Ile group, we observed a reduced responsiveness to LPS compared to WT TLR4. Taken together, we observed that the TLR4 Asp299Gly variant, but not the Thr399Ile variant, is responsible for impaired responsiveness of TLR4 to LPS and corresponding activation of NF-κB.